Low-dielectric heat-conducting gel and preparation method thereof
Through modified nano -composite particles to fill the silicon gel, combined with the technical means of zinc acetate and modified nano oxide, solve the problem of increased the viscosity of thermal silicon gel, and achieve the effect of high heat conduction, anti -penetration, antibacterial effect Essence
Patent Information
- Application Number
- CN202411497441.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
When the existing thermally conductive silicon gels increase in filling with thermally conductive fillers, their viscosity increases rapidly, resulting in the gel losing fluidity, resulting in defects such as pores, reducing thermal conductivity, and oil seepage.
Fill the silicon gel through modified nano -composite particles, and the modified nano -composite particles are made by combining zinc acetate with modified nano oxide, using micro -milk legal system to prepare modified nano oxide, and transform glucose into carbon elements through high temperature crickets. , Form the thermal network chain.
The effect of high thermal conductivity, anti -penetration, and antibacterial effects has been achieved, the heat dissipation effect is significantly improved, and the abrasion resistance and binding ability of the material is enhanced, and the phenomenon of separation is reduced.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermally conductive gels, in particular to a low dielectric thermally conductive gel and a preparation method thereof. Background Art
[0002] At present, the integration degree of electronic components is getting higher and higher, and the devices are developing towards light weight, small size, and high power density. Therefore, the heat generated inside them is getting larger and larger. The large amount of heat generated and accumulated inside the electronic components will greatly affect the service life of the electronic components or directly cause the electronic components to fail. Some scholars have proposed that the failure of Moore's Law is partly due to the large amount of heat generated by electronic components. Therefore, it has become an urgent problem to quickly and effectively discharge the large amount of heat generated by electronic components.
[0003] Thermally conductive silicone gel is a composite of liquid silicone rubber and thermally conductive filler. Its performance is between thermally conductive silicone grease and thermally conductive gasket. It has the advantages of both thermally conductive gasket and thermally conductive silicone grease, and has a tendency to gradually replace thermally conductive silicone grease and thermally conductive gasket. However, as the amount of thermally conductive filler increases, the viscosity of the gel system will increase rapidly, and even lose fluidity, resulting in defects such as pores in the cured gel, which greatly reduces the thermal conductivity of the material. In addition, due to the volatility of the matrix, thermally conductive gel will inevitably have oil seepage during long-term use. Therefore, it is necessary to invent a thermally conductive silicone gel that takes into account both thermal conductivity and low oil permeability. Summary of the invention
[0004] The object of the present invention is to provide a low dielectric thermal conductive gel and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a low dielectric thermal conductive gel, wherein the low dielectric thermal conductive gel is prepared by filling silicone gel with modified nano-composite particles.
[0006] Furthermore, the modified nano composite particles are prepared by combining zinc acetate with modified nano beryllium oxide in a spray form through a vacuum tightly coupled vacuum induction furnace.
[0007] Furthermore, the modified nano-beryllium oxide is prepared by obtaining nanoparticles from glucose and beryllium sulfate through a microemulsion method and then calcining at a high temperature.
[0008] Furthermore, a method for preparing a low dielectric thermal conductive gel comprises the following preparation steps:
[0009] (1) 17-29 parts of beryllium sulfate, 11-23 parts of glucose, and 102-174 parts of deionized water are mixed uniformly, 510-870 parts of cyclohexane, 51-87 parts of hexadecyltrimethylammonium bromide, and 26-44 parts of n-butanol are added, and the mixture is stirred at 40° C. and 2000 rpm for 20-50 min, 1 part of the mixture is added dropwise, and the mixture is stirred for 3-7 h, and allowed to stand for 16-32 h, and then placed in a centrifuge and centrifuged at 3000 r / min for 15 min, washed with ethanol three times, dried in an oven at 50-60° C. for 10-18 h, and then calcined at 850° C. for 5-9 h under nitrogen protection, and cooled to 25° C. to obtain modified nano-beryllia;
[0010] (2) 36 to 68 parts of modified nano-beryllium oxide are placed in a smelting crucible, and 41 to 73 parts of zinc acetate are melted to obtain a molten liquid, the crucible is placed in a furnace, and when the ambient temperature reaches 380° C., the molten liquid is atomized and sprayed to obtain modified nano-composite particles;
[0011] (3) 500-800 parts of methyl silicone resin, 41-67 parts of terminal hydroxyl silicone oil, 25-31 parts of modified nanocomposite particles, and 2-4 parts of ethynyl cyclohexanol are mixed uniformly, 0.4-0.8 parts of platinum catalyst are added, and the mixture is stirred at 1400 rpm for 15-25 minutes, and then placed in a vacuum oven at a vacuum degree of -0.09 MPa for vacuum degassing for 20-40 minutes to obtain a thermal conductive silicone gel.
[0012] Furthermore, the preparation method of the mixed solution in step (1) is as follows: 98 to 152 parts of aqueous ammonia, 503 to 859 parts of cyclohexane, 46 to 72 parts of hexadecyltrimethylammonium bromide, and 23 to 35 parts of n-butanol are stirred at 35° C. and 1800 rpm for 25 to 45 minutes to obtain a mixed solution.
[0013] Furthermore, the atomization spraying conditions in step (2) are: atomization medium Ar gas, atomization pressure 2.8-3.6 MPa, atomization flow rate 22-28 m 3 / min.
[0014] Furthermore, the model of the methyl silicone resin in step (3) is SI-MQ102.
[0015] Furthermore, the mass fraction of active hydrogen in the terminal hydroxyl silicone oil in step (3) is 0.07%.
[0016] Furthermore, the model of the ethynyl cyclohexanol in step (3) is DX-3022.
[0017] Furthermore, the platinum atomic mass fraction of the platinum catalyst in step (3) is 0.4%.
[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0019] The present invention utilizes modified nano composite particles to fill silicone gel to achieve the effects of high thermal conductivity, anti-seepage and antibacterial.
[0020] The invention uses a microemulsion method to prepare modified nano beryllium oxide from glucose and beryllium sulfate. The modified nano beryllium oxide has good dispersibility and thermal stability, fills the tiny gap between the electronic component and the radiator, removes air, thereby forming a continuous heat conduction channel, significantly improving the heat dissipation effect, and at the same time enhancing the bonding ability with the silicone gel, reducing the separation phenomenon, and thus achieving the anti-seepage effect; on this basis, high-temperature calcination is used to convert the glucose into carbon elements, which are evenly distributed in the beryllium oxide to form a heat conduction network chain, thereby greatly improving the thermal conductivity; zinc acetate is then combined with the modified nano beryllium oxide in a spray form through a tightly coupled vacuum induction furnace to form particles with smooth surfaces, which enter the friction surface to form a lubricating film, reduce the roughness of the metal surface, enhance the wear resistance, and further densify the carbon elements in the modified nano beryllium oxide, thereby enhancing the anti-seepage ability; the metal zinc ions introduced by the zinc acetate significantly enhance the thermal conductivity and heat dissipation ability of the material, and can interact with the negative ions of the bacterial cells, thereby destroying the biofilm and metabolic basis thereof, thereby achieving the effect of inhibiting and killing bacteria. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the low dielectric thermal conductivity gel prepared in the following examples are as follows:
[0023] Thermal conductivity: After the same mass of the embodiment and the comparative example are completely cured, the test is performed according to ASTM-D5470.
[0024] Antibacterial rate: Take the same mass of the embodiment and the comparative example and use the direct contact method to test the antibacterial performance of the material.
[0025] Oil permeability: Take the same mass of the embodiment and the comparative example to make a cylindrical silicone gel sample with a diameter of 30 mm and a height of 50 mm, place it on filter paper and keep it in an oven at 60°C for 168 hours, remove the silicone gel and weigh the change in the mass of the filter paper.
[0026] Example 1
[0027] (1) 98 parts of aqueous ammonia, 503 parts of cyclohexane, 46 parts of hexadecyltrimethylammonium bromide, and 23 parts of n-butanol were stirred at 35° C. and 1800 rpm for 25 min to prepare a mixed solution;
[0028] (2) 17 parts of beryllium sulfate, 11 parts of glucose, and 102 parts of deionized water were mixed uniformly, 510 parts of cyclohexane, 51 parts of hexadecyltrimethylammonium bromide, and 26 parts of n-butanol were added, and the mixture was stirred at 40°C and 2000 rpm for 20 min, 1 part of the mixture was added dropwise, and the mixture was stirred for 3 h, and allowed to stand for 16 h. The mixture was centrifuged at 3000 r / min for 15 min, washed with ethanol 3 times, dried in an oven at 50°C for 10 h, and then calcined at 850°C for 5 h under nitrogen protection, and cooled to 25°C to obtain modified nano-beryllium oxide;
[0029] (3) 36 parts of modified nano-beryllium oxide were placed in a smelting crucible, and 41 parts of zinc acetate were melted to obtain a molten liquid. The crucible was placed in a furnace. When the ambient temperature reached 380°C, the atomizing medium was Ar gas, the atomizing pressure was 2.8 MPa, and the atomizing flow rate was 22 m 3 / min atomizing and spraying the melt to obtain modified nanocomposite particles;
[0030] (4) 500 parts of SI-MQ102 methyl silicone resin, 41 parts of terminal hydroxyl silicone oil with an active hydrogen mass fraction of 0.07%, 25 parts of modified nanocomposite particles, and 2 parts of DX-3022 ethynyl cyclohexanol were mixed evenly, and 0.4 parts of a platinum catalyst with a platinum atomic mass fraction of 0.4% were added and stirred at 1400 rpm for 15 minutes. The mixture was then placed in a vacuum oven at a vacuum degree of -0.09 MPa for vacuum degassing for 20 minutes to obtain a thermal conductive silicone gel.
[0031] Example 2
[0032] (1) 125 parts of aqueous ammonia, 681 parts of cyclohexane, 59 parts of hexadecyltrimethylammonium bromide, and 29 parts of n-butanol were stirred at 35° C. and 1800 rpm for 35 minutes to prepare a mixed solution;
[0033] (2) 23 parts of beryllium sulfate, 17 parts of glucose, and 138 parts of deionized water were mixed uniformly, 690 parts of cyclohexane, 69 parts of hexadecyltrimethylammonium bromide, and 35 parts of n-butanol were added, and the mixture was stirred at 40°C and 2000 rpm for 35 minutes, 1 part of the mixture was added dropwise, and the mixture was stirred for 5 hours, and allowed to stand for 24 hours. The mixture was centrifuged at 3000 r / min for 15 minutes, washed with ethanol three times, dried in an oven at 55°C for 14 hours, and then calcined at 850°C for 7 hours under nitrogen protection, and cooled to 25°C to obtain modified nano-beryllium oxide;
[0034] (3) 52 parts of modified nano-beryllium oxide were placed in a smelting crucible, and 57 parts of zinc acetate were melted to obtain a molten liquid. The crucible was placed in a furnace. When the ambient temperature reached 380°C, an atomizing medium of Ar gas was used, the atomizing pressure was 3.2 MPa, and the atomizing flow rate was 25 m 3 / min atomizing and spraying the melt to obtain modified nanocomposite particles;
[0035] (4) 650 parts of SI-MQ102 methyl silicone resin, 54 parts of terminal hydroxyl silicone oil with an active hydrogen mass fraction of 0.07%, 28 parts of modified nanocomposite particles, and 3 parts of DX-3022 ethynyl cyclohexanol were mixed evenly, and 0.6 parts of a platinum catalyst with a platinum atomic mass fraction of 0.4% were added and stirred at 1400 rpm for 20 minutes. Then, the mixture was placed in a vacuum oven at a vacuum degree of -0.09 MPa for vacuum degassing for 30 minutes to obtain a thermal conductive silicone gel.
[0036] Example 3
[0037] (1) 152 parts of aqueous ammonia, 859 parts of cyclohexane, 72 parts of hexadecyltrimethylammonium bromide, and 35 parts of n-butanol were stirred at 35° C. and 1800 rpm for 45 minutes to prepare a mixed solution;
[0038] (2) 29 parts of beryllium sulfate, 23 parts of glucose, and 174 parts of deionized water were mixed uniformly, 870 parts of cyclohexane, 87 parts of hexadecyltrimethylammonium bromide, and 44 parts of n-butanol were added, and the mixture was stirred at 40°C and 2000 rpm for 50 min, 1 part of the mixture was added dropwise, and the mixture was stirred for 7 h, and allowed to stand for 32 h. The mixture was centrifuged at 3000 r / min for 15 min, washed with ethanol 3 times, dried in an oven at 60°C for 18 h, and then calcined at 850°C for 9 h under nitrogen protection, and cooled to 25°C to obtain modified nano-beryllum oxide;
[0039] (3) 68 parts of modified nano-beryllium oxide were placed in a smelting crucible, and 73 parts of zinc acetate were melted to obtain a molten liquid. The crucible was placed in a furnace. When the ambient temperature reached 380°C, the atomizing medium was Ar gas, the atomizing pressure was 3.6 MPa, and the atomizing flow rate was 28 m 3 / min atomizing and spraying the melt to obtain modified nanocomposite particles;
[0040] (4) 800 parts of SI-MQ102 methyl silicone resin, 67 parts of terminal hydroxyl silicone oil with an active hydrogen mass fraction of 0.07%, 31 parts of modified nanocomposite particles, and 4 parts of DX-3022 ethynyl cyclohexanol were mixed evenly, 0.8 parts of a platinum catalyst with a platinum atomic mass fraction of 0.4% were added, and the mixture was stirred at 1400 rpm for 25 minutes. The mixture was then placed in a vacuum oven at a vacuum degree of -0.09 MPa for vacuum degassing for 40 minutes to obtain a thermal conductive silicone gel.
[0041] Comparative Example 1
[0042] The difference between Comparative Example 1 and Example 2 is that step (2) is different. Step (2) is changed to: 23 parts of beryllium sulfate and 138 parts of deionized water are mixed evenly, 690 parts of cyclohexane, 69 parts of hexadecyltrimethylammonium bromide and 35 parts of n-butanol are added, and the mixture is stirred at 40° C. and 2000 rpm for 35 minutes, 1 part of the mixture is added dropwise, and the mixture is stirred for 5 hours, and the mixture is allowed to stand for 24 hours, and the mixture is centrifuged at 3000 r / min for 15 minutes in a centrifuge, washed with ethanol 3 times, dried in an oven at 55° C. for 14 hours, and then calcined at 850° C. for 7 hours under nitrogen protection, and cooled to 25° C. to obtain modified nano-beryllium oxide. The remaining steps are the same as those in Example 2.
[0043] Comparative Example 2
[0044] The difference between Comparative Example 2 and Example 2 is that step (2) is different. Step (2) is changed to: 17 parts of glucose and 138 parts of deionized water are mixed evenly, 690 parts of cyclohexane, 69 parts of hexadecyltrimethylammonium bromide, and 35 parts of n-butanol are added, and stirred at 40°C and 2000rpm for 35min, 1 part of the mixed solution is added dropwise, stirring is continued for 5h, and the mixture is allowed to stand for 24h. The mixture is placed in a centrifuge and centrifuged at 3000r / min for 15min. The mixture is washed 3 times with ethanol, dried in an oven at 55°C for 14h, and then calcined at 850°C for 7h under nitrogen protection, and cooled to 25°C to obtain modified nano carbon black; step (3) is changed to: 52 parts of modified nano carbon black are loaded into a melting crucible, and 57 parts of zinc acetate are melted to obtain a melt, the crucible is loaded into a furnace, and when the ambient temperature reaches 380°C, an atomizing medium is Ar gas, an atomizing pressure of 3.2MPa, and an atomizing flow rate of 25m 3 / min atomizing and spraying the melt to obtain modified nanocomposite particles. The remaining steps are the same as those in Example 2.
[0045] Comparative Example 3
[0046] The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: 23 parts of beryllium sulfate, 17 parts of glucose, and 138 parts of deionized water are mixed evenly, 690 parts of cyclohexane, 69 parts of hexadecyltrimethylammonium bromide, and 35 parts of n-butanol are added, and the mixture is stirred at 40° C. and 2000 rpm for 35 minutes, 1 part of the mixture is added dropwise, and the mixture is stirred for 5 hours, and the mixture is allowed to stand for 24 hours, and the mixture is placed in a centrifuge and centrifuged at 3000 r / min for 15 minutes, washed with ethanol 3 times, and dried in an oven at 55° C. for 14 hours to obtain modified nano-beryllum oxide. The remaining steps are the same as those in Example 2.
[0047] Comparative Example 4
[0048] The difference between Comparative Example 4 and Example 2 is that there is no step (3), and step (4) is changed to: 650 parts of SI-MQ102 methyl silicone resin, 54 parts of terminal hydroxyl silicone oil with an active hydrogen mass fraction of 0.07%, 28 parts of modified nano-beryllia, and 3 parts of DX-3022 ethynylcyclohexanol are mixed uniformly, 0.6 parts of platinum catalyst with a platinum atomic mass fraction of 0.4% are added, and stirred at a high speed of 1400 rpm for 20 minutes, and then placed in a vacuum oven at a vacuum degree of -0.09 MPa for vacuum degassing for 30 minutes to obtain a thermally conductive silicone gel. The remaining steps are the same as those of Example 2.
[0049] Comparative Example 5
[0050] The difference between Comparative Example 5 and Example 2 is that there is no step (3), and step (2) is changed to: 23 parts of beryllium sulfate, 17 parts of glucose, and 138 parts of deionized water are mixed uniformly, 690 parts of cyclohexane, 69 parts of hexadecyltrimethylammonium bromide, and 35 parts of n-butanol are added, and the mixture is stirred at 40° C. and 2000 rpm for 35 minutes, 1 part of the mixed solution is added dropwise, and the mixture is stirred for 5 hours, and the mixture is allowed to stand for 24 hours, and the mixture is placed in a centrifuge and centrifuged at 3000 r / min for 15 minutes, washed with ethanol 3 times, and dried in an oven at 55° C. for 14 hours, and then a 2.5 g / L zinc acetate aqueous solution is sprayed under nitrogen protection, and the mixture is calcined at 850° C. for 7 hours, and cooled to 25° C. to obtain modified nano-berylium oxide. The remaining steps are the same as those in Example 2.
[0051] Effect example
[0052] Table 1 below shows the performance analysis results of the low dielectric thermal conductive gels of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0053] Table 1
[0054] <![CDATA[Thermal conductivity / W·m·k -1 > Antibacterial rate / % Oil permeability / mg Example 1 5.34 97.2 6 Example 2 5.40 97.6 5 Example 3 5.38 97.5 6 Comparative Example 1 3.97 95.3 59 Comparative Example 2 2.14 94.8 68 Comparative Example 3 3.46 96.1 31 Comparative Example 4 3.68 76.9 24 Comparative Example 5 2.73 96.0 97
[0055] From the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 1, it can be found that the addition of glucose can be evenly distributed in beryllium oxide, enhance the binding ability with silicone gel, reduce the separation phenomenon, and achieve the anti-seepage effect; from the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 2, it can be found that beryllium sulfate is made into nano-beryllium oxide by the microemulsion method, which has good dispersibility and thermal stability, fills the tiny gaps between electronic components and radiators, excludes air, forms a continuous heat conduction channel, significantly improves the heat dissipation effect, and enhances the binding ability with silicone gel, reduces the separation phenomenon, and achieves the anti-seepage effect; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 3, it can be found that glucose is converted into carbon element under high-temperature calcination and is tightly combined with beryllium oxide. , and a heat-conducting network chain is formed therein, greatly improving the thermal conductivity; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 4, it can be found that the metal zinc ions introduced by zinc acetate significantly enhance the thermal conductivity and heat dissipation capabilities of the material, and can interact with the negative ions of bacterial cells, thereby destroying their biofilms and metabolic basis, and achieving the effect of inhibiting and killing bacteria; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 5, it can be found that zinc acetate is melted in a tightly coupled vacuum induction furnace and combined with modified nano-beryllium oxide in a spray form to form particles with smooth surfaces, which enter the friction surface to form a lubricating film, reduce the roughness of the metal surface, enhance wear resistance, and at the same time further densify the carbon element in the modified nano-beryllium oxide, further enhancing the anti-seepage ability.
[0056] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A low dielectric thermal conductive gel, characterized in that: The low dielectric thermal conductive gel is prepared by filling silicone gel with modified nano composite particles.
2. A low dielectric thermal conductive gel according to claim 1, characterized in that: The modified nano composite particles are prepared by combining zinc acetate with modified nano beryllium oxide in a spray form through a vacuum tightly coupled vacuum induction furnace.
3. A low dielectric thermal conductive gel according to claim 2, characterized in that: The modified nanometer beryllium oxide is prepared by obtaining nanometer particles from glucose and beryllium sulfate through a microemulsion method and then calcining at a high temperature.
4. A method for preparing a low dielectric thermal conductive gel, characterized in that: The method comprises the following preparation steps: (1) 17-29 parts of beryllium sulfate, 11-23 parts of glucose, and 102-174 parts of deionized water are mixed uniformly, 510-870 parts of cyclohexane, 51-87 parts of hexadecyltrimethylammonium bromide, and 26-44 parts of n-butanol are added, and the mixture is stirred at 40° C. and 2000 rpm for 20-50 min, 1 part of the mixture is added dropwise, and the mixture is stirred for 3-7 h, and allowed to stand for 16-32 h, and then placed in a centrifuge and centrifuged at 3000 r / min for 15 min, washed with ethanol three times, dried in an oven at 50-60° C. for 10-18 h, and then calcined at 850° C. for 5-9 h under nitrogen protection, and cooled to 25° C. to obtain modified nano-beryllia; (2) 36-68 parts of modified nano-beryllium oxide are loaded into a smelting crucible, and 41-73 parts of zinc acetate are melted to obtain a molten liquid, the crucible is loaded into a furnace, and when the ambient temperature reaches 380° C., the molten liquid is atomized and sprayed to obtain modified nano-composite particles; (3) 500-800 parts of methyl silicone resin, 41-67 parts of terminal hydroxyl silicone oil, 25-31 parts of modified nanocomposite particles, and 2-4 parts of ethynyl cyclohexanol were mixed uniformly, 0.4-0.8 parts of platinum catalyst were added, and the mixture was stirred at 1400 rpm for 15-25 minutes, and then placed in a vacuum oven at a vacuum degree of -0.09 MPa for vacuum degassing for 20-40 minutes to obtain a thermal conductive silicone gel.
5. The method for preparing a low dielectric thermal conductive gel according to claim 4, characterized in that: The preparation method of the mixed solution in step (1) is as follows: 98 to 152 parts of aqueous ammonia, 503 to 859 parts of cyclohexane, 46 to 72 parts of hexadecyltrimethylammonium bromide, and 23 to 35 parts of n-butanol are stirred at 35° C. and 1800 rpm for 25 to 45 minutes to obtain a mixed solution.
6. The method for preparing a low dielectric thermal conductive gel according to claim 4, characterized in that: The atomization spraying conditions in step (2) are: atomization medium Ar gas, atomization pressure 2.8~3.6MPa, atomization flow rate 22~28m 3 / min.
7. The method for preparing a low dielectric thermal conductive gel according to claim 4, characterized in that: The model of the methyl silicone resin in step (3) is SI-MQ102.
8. The method for preparing a low dielectric thermal conductive gel according to claim 4, characterized in that: The mass fraction of active hydrogen in the terminal hydroxyl silicone oil in step (3) is 0.07%.
9. The method for preparing a low dielectric thermal conductive gel according to claim 4, characterized in that: The model of the ethynyl cyclohexanol in step (3) is DX-3022.
10. The method for preparing a low dielectric thermal conductive gel according to claim 4, characterized in that: The platinum atomic mass fraction of the platinum catalyst in step (3) is 0.4%.